The agriculture sector has what it takes to drive post-COVID-19 economic recovery - Verma, Smriti; Kumar, Anjani (2020)
If the government can ensure that the benefits of credit facilities reach farmers in a time-bound fashion, the sector could finally leapfrog into a new regime of growth and enhanced farmer welfare.